2021
DOI: 10.3390/ijms22147420
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Mitogen-Activated Protein Kinase Kinase 3 Negatively Regulates Hepatitis A Virus Replication

Abstract: Zinc chloride is known to be effective in combatting hepatitis A virus (HAV) infection, and zinc ions seem to be especially involved in Toll-like receptor (TLR) signaling pathways. In the present study, we examined this involvement in human hepatoma cell lines using a human TLR signaling target RT-PCR array. We also observed that zinc chloride inhibited mitogen-activated protein kinase kinase 3 (MAP2K3) expression, which could downregulate HAV replication in human hepatocytes. It is possible that zinc chloride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The suppression of La by specific small interfering RNAs (siRNAs) or by janus kinase (JAK) inhibitors (AZD1480, SD-1029, and AG490) leads to the efficient inhibition of HAV replication through the inhibition of HAV internal ribosomal entry-site (IRES) [113,114]. Recent studies have also demonstrated the ability of zinc compounds [115][116][117] and the enzyme heme oxygenase-1 (HO-1) [118], a stress-inducible heat shock protein, to inhibit viral replication in cell culture.…”
Section: Research On Hav Antiviral Treatmentmentioning
confidence: 99%
“…The suppression of La by specific small interfering RNAs (siRNAs) or by janus kinase (JAK) inhibitors (AZD1480, SD-1029, and AG490) leads to the efficient inhibition of HAV replication through the inhibition of HAV internal ribosomal entry-site (IRES) [113,114]. Recent studies have also demonstrated the ability of zinc compounds [115][116][117] and the enzyme heme oxygenase-1 (HO-1) [118], a stress-inducible heat shock protein, to inhibit viral replication in cell culture.…”
Section: Research On Hav Antiviral Treatmentmentioning
confidence: 99%
“…MP2K3 is a bispecific kinase belonging to the MAP kinase family. It is activated by inflammation and endoplasmic reticulum stress, phosphorylates and activates the 38 mitogen-activated protein kinase axis, and participates in cell growth, differentiation, apoptosis, movement, and inflammation ( 23 ). In addition, studies have shown that MP2K3 may also be involved in the EMT of primary tumor cells ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and endoplasmic reticulum (ER) stress stimulate MAPK3, which phosphorylates and triggers p38 MAPK. Insulin could also activate MAPK3, which is necessary for glucose transporter expression [ 66 ]. Zinc sulfate is more likely to boost the anti-HAV action related to interferon-alpha-2a, whereas zinc chloride significantly improves it.…”
Section: Hav Ratementioning
confidence: 99%